2022
DOI: 10.1001/jamaoto.2021.2824
|View full text |Cite
|
Sign up to set email alerts
|

Clinician Attitudes and Beliefs About Deintensifying Head and Neck Cancer Surveillance

Abstract: Surveillance imaging and visits are costly and have not been shown to improve oncologic outcomes for patients with head and neck cancer (HNC). However, the benefit of surveillance visits may extend beyond recurrence detection. To better understand surveillance and potentially develop protocols to tailor current surveillance paradigms, it is important to elicit the perspectives of the clinicians who care for patients with HNC. OBJECTIVE To characterize current surveillance practices and explore clinician attitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Given that the frequency of visits decreases over time in follow‐up care, one might think that a patient's needs, fears and anxieties would decrease to correspond with less visits. A recent qualitative study demonstrated that physicians do believe that patients have ongoing requirements throughout the follow‐up period (Chen et al, 2021). Our work confirmed this and quantifies these requirements from a patient perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the frequency of visits decreases over time in follow‐up care, one might think that a patient's needs, fears and anxieties would decrease to correspond with less visits. A recent qualitative study demonstrated that physicians do believe that patients have ongoing requirements throughout the follow‐up period (Chen et al, 2021). Our work confirmed this and quantifies these requirements from a patient perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, physicians reported low-risk disease as being a facilitator for lengthening follow-up intervals. 1 We would argue the contrary. It is well established that patients with advanced initial-stage disease, especially if coupled with a short disease-free interval, will have extremely poor salvage treatment outcomes.…”
mentioning
confidence: 90%
“…As more patients with head and neck cancer benefit from a quantity-of-life perspective from more advanced radiation delivery systems, chemoimmunotherapy breakthroughs, and improved surgical techniques, the impending impact this has on resources needed in surveillance, such as costs associated with specialty examinations and anatomic imaging studies, as well as the psychosocial and financial impact on the patients themselves, is becoming more prevalent. In the Original Investigation by Chen et al, 1 the authors seek to identify physician and patientrelated barriers to deintensifying surveillance practices and provide suggestions on facilitating change.…”
mentioning
confidence: 99%
See 2 more Smart Citations